2021
DOI: 10.1186/s13756-021-01004-8
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak investigation of Burkholderia cepacia infections related with contaminated chlorhexidine mouthwash solution in a tertiary care center in Turkey

Abstract: Background We report a nosocomial outbreak caused by Burkholderia cepacia that occurred among six patients admitted in the medical and surgical intensive care unit between 04 March 2019 and 02 April 2019 in Istanbul, Turkey. Methods The outbreak investigation was launched on 11 March 2019 five days after the detection of B. cepacia in four different patients. We defined potential reservoirs and started environmental screening. We sampled the liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It turned out to be a batch of MWS with chlorhexidine that had been used in the clinical management of the patients. Five of the six patients died despite the antibiotic therapies provided, although the retrospective analysis ruled out that the cause of death of one of the patients was Bcc infection [ 16 ].…”
Section: Outbreaks Of Nosocomial Infections By Bccmentioning
confidence: 99%
See 2 more Smart Citations
“…It turned out to be a batch of MWS with chlorhexidine that had been used in the clinical management of the patients. Five of the six patients died despite the antibiotic therapies provided, although the retrospective analysis ruled out that the cause of death of one of the patients was Bcc infection [ 16 ].…”
Section: Outbreaks Of Nosocomial Infections By Bccmentioning
confidence: 99%
“…Furthermore, the combination of available diagnostic and epidemiological tools is essential to distinguish Bcc infections in a timely manner, allowing an appropriate clinical approach to affected individuals. However, the constant search for and notification of cases of nosocomial infections due to Bcc are not mandatory practices in different cities and nations [ 6 , 16 ], which contributes to the constant risk for people with certain predisposing characteristics, such as those suffering from chronic obstructive pulmonary disease (COPD), ventilator‑associated pneumonia (VAP) [ 18 ], or CF [ 1 , 5 , 19 ].…”
Section: Outbreaks Of Nosocomial Infections By Bccmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] The oragnism's natural tendency to colonise various surfaces, intra-venous sets, centrallines, nebulizers, respiratory devices and disinfectants makes it a major cause for small hospital outbreaks. [7] Here, we present a series of five cases where an unusual violet pigment producing BCC was identified. To the best of our knowledge this is the first case of violet pigment producing BCC from Mumbai.…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been indicated in chronic nosocomial infections such as septicemia, respiratory tract infections, genitourinary system infections, intracranial infections, endocarditis, gastrointestinal system infections, and surgical site infections. 2 It is classified as an important emerging opportunistic pathogen, especially in immunocompromised hosts. Studies have shown that these bacteria maintain their vitality by attaching to any surface and forming biofilms rather than remaining in their planktonic 3 In addition to having an important role in bacterial adherence and resistance to antibiotics and phagocytosis, biofilms allow bacteria to gain the ability to adapt to the environment by forming a community with new genetic modulations.…”
Section: Introductionmentioning
confidence: 99%